2017
DOI: 10.1186/s40349-017-0088-9
|View full text |Cite
|
Sign up to set email alerts
|

Moderate-to-deep sedation technique, using propofol and ketamine, allowing synchronised breathing for magnetic resonance high-intensity focused ultrasound (MR-HIFU) treatment for uterine fibroids: a pilot study

Abstract: BackgroundMagnetic resonance high-intensity focused ultrasound (MR-HIFU) treatment for uterine fibroids is rapidly gaining popularity as a treatment modality. This procedure is generally uncomfortable, painful, and requires minimal or absence of movement and an MR-HIFU synchronised breathing pattern of the patient. Procedural sedation and analgesia protocols have become the standard practice in interventional radiology departments worldwide. The aim of this study was to explore if a sedation regimen with low-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…To reduce failures as a result of experienced pain by the patient, our sedation protocol was optimized. Procedural Sedation and Analgesia (PSA) is increasingly used during uncomfortable radiological interventions and is also suitable for the MR-HIFU treatment of fibroids [ 22 , 23 ]. Sedation is performed to prevent the patient from deep visceral pain, hot sensations on the skin and motion artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce failures as a result of experienced pain by the patient, our sedation protocol was optimized. Procedural Sedation and Analgesia (PSA) is increasingly used during uncomfortable radiological interventions and is also suitable for the MR-HIFU treatment of fibroids [ 22 , 23 ]. Sedation is performed to prevent the patient from deep visceral pain, hot sensations on the skin and motion artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that esketamine nasal spray could cause transient and asymptomatic blood pressure elevations [33]. Therefore, there has been growing interest in the use of esketamine as an ideal adjunct to propofol for procedural sedation and analgesia [12,34]. It was reported that the use of a combination of propofol and esketamine for procedural analgesia and sedation during MR-guided HIFU treatments of uterine fibroids is feasible and safe, with a short recovery time and a low risk of major adverse events [34].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there has been growing interest in the use of esketamine as an ideal adjunct to propofol for procedural sedation and analgesia [12,34]. It was reported that the use of a combination of propofol and esketamine for procedural analgesia and sedation during MR-guided HIFU treatments of uterine fibroids is feasible and safe, with a short recovery time and a low risk of major adverse events [34]. Recently, Eberl, S. et al demonstrated low-dose esketamine reduces the requirement of propofol for sedation during ERCP in ASA I-II patients without affecting recovery time, side effects, cardiovascular or respiratory adverse events and satisfaction of endoscopists and patients, when compared with alfentanil [12].…”
Section: Discussionmentioning
confidence: 99%
“…Although HIFU treatment of uterine adenomyosis may be less invasive than treatment of other intraabdominal organs, it still requires appropriate control of both visceral and somatic pain in addition to the administration of sedatives. The MAC procedure that utilized remifentanil, fentanyl, midazolam, and a combination of antiemetics may be more popular than EA in the HIFU treatment of uterine adenomyosis [27]. However, intravenous infusion of remifentanil could not satisfactorily eliminate nociceptive pain such as somatic pain in the abdominal wall or visceral pain originating from the parietal peritoneum during HIFU treatment [28].…”
Section: Discussionmentioning
confidence: 99%